Morphophysiological and yield traits of soybean varieties tolerant of intercropping with maize - INDAH PERMANASARI; ENDANG SULISTYANINGSIH; BUDIASTUTI KURNIASIH; DIDIK INDRADEWA (Society for Indonesian Biodiversity, 2023)
Abstract. Permanasari I, Sulistyaningsih E, Kurniasih B, Indradewa D. 2023. Morphophysiological and yield traits of soybean varieties tolerant of intercropping with maize. Biodiversitas 24: 3872-3880. Not all soybean varieties grow optimally when intercropped with maize. Previously, we identified seven varieties (i.e.,